Activity Index and Lotka's Law Application with Diabetes and Allied Diseases in India During 1995–2013 - Baskaran, C.; Karuilancheran, C. (Journal of Information and Knowledge, 2015)
This paper describes the relative growth rate and doubling time and activity index and Lotka's law apply on the publications of diabetes and allied diseases during 1995-2013. The study found that steady growth rate in terms of productivity was observed throughout the period of study. There was a sudden increase noticed in 2002, 2009, and 2012 while a declining trend was observed in 1996, 2003, and 2013. The calculated values of Maximum Likelihood Estimator, n and k are 0.24, 2.66 and 0.78 respectively. The C.V. at 0.05 significant level for 29 degrees of freedom is 42.56 and the calculated value of Chi-Square (X2) obtained in this case is 5309.368. Afterwords, the performance of researchers started diminishing. It was supported by SPI that ranges between 9 and 10 only.